1997
DOI: 10.1136/bjo.81.6.497
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase chain reaction for detection of Chlamydia trachomatis in conjunctival swabs

Abstract: Aims/background-OcularChlamydia trachomatis infection in the west occurs as ophthalmia neonatorum, acquired from the mother, or adult paratrachoma which is also associated with current genital tract infection. Accurate rapid laboratory diagnosis facilitates management, but the relative merits of antigen detection or DNA amplification tests are unresolved. Methods-A polymerase chain reaction (PCR) test was developed which amplified part of the plasmid shared by all the serovars of C trachomatis. Conjunctival sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
3

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 29 publications
0
9
0
3
Order By: Relevance
“…Although DNA extraction and amplification (NAATs) are known to be more sensitive than Giemsa staining and microimmunofluorescence (MIF) for the detection of Chlamydia in human conjunctiva (20)(21)(22)(23), this study's funding would not cover the cost of the most sensitive options. Therefore, two samples were obtained from each child by scraping the conjunctiva.…”
Section: Trachomatis Detectionmentioning
confidence: 99%
“…Although DNA extraction and amplification (NAATs) are known to be more sensitive than Giemsa staining and microimmunofluorescence (MIF) for the detection of Chlamydia in human conjunctiva (20)(21)(22)(23), this study's funding would not cover the cost of the most sensitive options. Therefore, two samples were obtained from each child by scraping the conjunctiva.…”
Section: Trachomatis Detectionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Assays targeting Candida, Aspergillus, and Fusarium have been tested preliminarily in vitreous specimens, 28 29 and recently an assay using panfungal primers has been used more extensively in India. 30 A PCR assay has also been applied to detect Fusarium in rabbit corneal infections.…”
mentioning
confidence: 99%
“…Fan et al [7] found that PCR was positive for Chlamydia trachomatis in 63% of 49 patients with follicular conjunctivitis, while Haller et al [8] found that 8.6% of their patients were positive to this microorganism by PCR and cell culture. Elnifro et al [6] reported as many as 27% of patients to be positive for Chlamydia by PCR. However, in all previous studies, no distinction was made between acute and chronic follicular conjunctivitis.…”
Section: Discussionmentioning
confidence: 99%